Brazilian Guidelines for In-office and Out-of-office Blood Pressure Measurement – 2023 - Feitosa, Audes Diógenes de Magalhães (2023)
Hypertension is one of the primary modifiable risk factors for morbidity and mortality worldwide, being a major risk factor for coronary artery disease, stroke, and kidney failure. Furthermore, it is highly prevalent, affecting more than one-third of the global population. Blood pressure measurement is a MANDATORY procedure in any medical care setting and is carried out by various healthcare professionals. However, it is still commonly performed without the necessary technical care. Since the diagnosis relies on blood pressure measurement, it is clear how important it is to handle the techniques, methods, and equipment used in its execution with care. It should be emphasized that once the diagnosis is made, all short-term, medium-term, and long-term investigations and treatments are based on the results of blood pressure measurement. Therefore, improper techniques and/or equipment can lead to incorrect diagnoses, either underestimating or overestimating values, resulting in inappropriate actions and significant health and economic losses for individuals and nations. Once the correct diagnosis is made, as knowledge of the importance of proper treatment advances, with the adoption of more detailed normal values and careful treatment objectives towards achieving stricter blood pressure goals, the importance of precision in blood pressure measurement is also reinforced. Blood pressure measurement (described below) is usually performed using the traditional method, the so-called casual or office measurement. Over time, alternatives have been added to it, through the use of semi-automatic or automatic devices by the patients themselves, in waiting rooms or outside the office, in their own homes, or in public spaces. A step further was taken with the use of semi-automatic devices equipped with memory that allow sequential measurements outside the office (ABPM; or HBPM) and other automatic devices that allow programmed measurements over longer periods (HBPM). Some aspects of blood pressure measurement can interfere with obtaining reliable results and, consequently, cause harm in decision-making. These include the importance of using average values, the variation in blood pressure during the day, and short-term variability. These aspects have encouraged the performance of a greater number of measurements in various situations, and different guidelines have advocated the use of equipment that promotes these actions. Devices that perform HBPM or ABPM, which, in addition to allowing greater precision, when used together, detect white coat hypertension (WCH), masked hypertension (MH), sleep blood pressure alterations, and resistant hypertension (RHT) (defined in Chapter 2 of this guideline), are gaining more and more importance. Taking these details into account, we must emphasize that information related to diagnosis, classification, and goal setting is still based on office blood pressure measurement, and for this reason, all attention must be given to the proper execution of this procedure.